2009
DOI: 10.1162/coli.06-77-prep13
|View full text |Cite
|
Sign up to set email alerts
|

The Syntax and Semantics of Prepositions in the Task of Automatic Interpretation of Nominal Phrases and Compounds: A Cross-Linguistic Study

Abstract: In this article we explore the syntactic and semantic properties of prepositions in the context of the semantic interpretation of nominal phrases and compounds. We investigate the problem based on cross-linguistic evidence from a set of six languages: English, Spanish, Italian, French, Portuguese, and Romanian. The focus on English and Romance languages is well motivated. Most of the time, English nominal phrases and compounds translate into constructions of the form N P N in Romance languages, where the P (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…For example, Levi would interpret truck driver as PATIENT, in the sense that truck is the patient of the underlying verb of the head noun to drive, whereas Lauer would interpret it as OF (c.f., driver of (the) truck). Girju (2007Girju ( , 2009 leveraged translation data to improve the accuracy of compound noun interpretation, based on the observation that the choice of preposition in Romance languages is often indicative of the semantics of the compound noun. Conversely, Johnston and Busa (1996) used Qualia structure from the Generative Lexicon (Pustejovsky 1995) to interpret the prepositions in Italian complex nominals, such as macchina da corsa "race car".…”
Section: The Semantics Of Prepositional Mwesmentioning
confidence: 99%
“…For example, Levi would interpret truck driver as PATIENT, in the sense that truck is the patient of the underlying verb of the head noun to drive, whereas Lauer would interpret it as OF (c.f., driver of (the) truck). Girju (2007Girju ( , 2009 leveraged translation data to improve the accuracy of compound noun interpretation, based on the observation that the choice of preposition in Romance languages is often indicative of the semantics of the compound noun. Conversely, Johnston and Busa (1996) used Qualia structure from the Generative Lexicon (Pustejovsky 1995) to interpret the prepositions in Italian complex nominals, such as macchina da corsa "race car".…”
Section: The Semantics Of Prepositional Mwesmentioning
confidence: 99%
“…Second, prepositions need to be researched because they constitute a productive grammatical resource in English and in many other languages. According to Fang as cited in Girju, there is one preposition in ten English words in a corpus of one million words [5].…”
Section: Introductionmentioning
confidence: 99%
“…Coventry, Carmichael and Garrod investigated the semantics of spatial prepositions aiming to specify general factors of a functional geometry as also examined in Coventry and Garrod, Coventry and Olivier, and Coventry [6][7][8][9]. Another study was undertaken Girju which examines the syntax and semantics of prepositions in the context of the interpretation of nominal phrases and compounds based on cross-linguistic evidence from a set of six languages: English, Spanish, Italian, French, Portuguese, and Romanian [5]. Meanwhile, Tahaineh conducted a crosssectional investigation on interlingual and intralingual errors of the use of English prepositions by Arab-Jordanian undergraduate students [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although a semantic classification of prepositions lies beyond the scope of the present work (for a more detailed discussion on the Semantics of prepositions, see Girju, 2009), it is worthwhile to mention that they are highly polysemic words, that they can be assigned different semantic roles -agent, theme, experiencer, etc., -and that they can be assigned different semantic load: spatial, temporal, manner, purpose, etc.…”
Section: The Context Of Brazilian Immigration To South Floridamentioning
confidence: 99%
“…A number of studies has shown that prepositions account for a seizable portion of the total number of words in different corpora of English and Spanish (Girju, 2009). …”
mentioning
confidence: 99%